Adhesive Composition

JP7631026B2Active Publication Date: 2025-02-18SAKATA INX
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2021030761
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-26
Publication Date
2025-02-18
Estimated Expiration
2041-02-26

AI Technical Summary

Benefits of technology

【0006】 本発明の接着剤によれば、接着後において、気泡、クラックの発生がなく、接着性、屈折率、耐熱性、高屈折に優れる接着剤組成物が得られるという顕著な効果を発揮できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007631026000001
    Figure 0007631026000001
  • Figure 0007631026000002
    Figure 0007631026000002
Patent Text Reader

Abstract

To provide an adhesive composition that does not cause bubbles or cracks after bonding and is excellent in adhesion, refractive index, heat resistance, and high refractivity.SOLUTION: An adhesive composition contains A. highly refractive metal oxide particles; B. a cyclic siloxane compound having two or more epoxy groups in each molecule; C. at least one selected from a polyfunctional thiol compound and an acid anhydride; and D. at least one selected from an alicyclic epoxy compound and an epoxy group-containing silane coupling agent.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an adhesive composition. [Background technology]

[0002] There is a demand for improved light extraction efficiency in phosphor dispersion plates (pyrex with phosphor dispersed) for LEDs used in automobiles, etc. One method for achieving this is to apply a coating agent with a low refractive index to the phosphor dispersion plate of the LED, which has a large difference in refractive index from air, in order to prevent a decrease in the extraction efficiency and to improve it.Specifically, the sapphire glass (refractive index 1.8) of the LED chip base material and the phosphor dispersion plate (refractive index 1.78) are currently bonded with a silicone adhesive (refractive index 1.4 to 1.5). Therefore, we investigated the possibility of reducing light loss by increasing the refractive index of the adhesive. Also, phosphor dispersion plates for LEDs used in automobiles and other applications are required to have a high level of heat resistance. Not only must they withstand high temperatures (e.g. 150°C) and long periods of time (e.g. 1000 hours), but they must also be able to withstand cycle tests that alternate between high and low temperatures. Compositions containing epoxy compounds and silane coupling agents have been studied as adhesives for bonding glass pieces together (see documents 1 to 4 below). In recent years, laminates made of multiple pieces of glass have been required to have a high refractive index, and adhesives for glass containing high refractive index materials such as zirconium oxide have been studied. In general, compositions comprising zirconium oxide and an epoxy compound are not practical because the reaction between the two tends to cause the composition to gel (become highly viscous). In addition, a composition consisting of zirconium oxide and a silane coupling agent is not practical because, after being formed into a coating film, the condensation reaction of the silane coupling agent tends to cause air bubbles to form and the transparency of the adhesive layer to decrease. Furthermore, when a polysiloxane-based substance such as a general silicone or cyclic siloxane is used in place of the silane coupling agent, the zirconium oxide does not disperse stably in the polysiloxane, and the transparency of the coating film is also insufficient. In order to prevent the generation of bubbles, the composition must be solvent-free. However, no adhesive that satisfies all of the above requirements has been developed to date. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 49-21410 [Patent Document 2] Japanese Patent Application Publication No. 8-26784 [Patent Document 3] International Publication No. 2018 / 194074 [Patent Document 4] International Publication No. 2016 / 98305 Summary of the Invention [Problem to be solved by the invention]

[0004] The problem to be solved by the present invention is to provide an adhesive composition for use in bonding components that transmit or diffuse light, which is free from the generation of air bubbles or cracks and has excellent adhesion, refractive index, heat resistance, and high refractive index. [Means for solving the problem]

[0005] Means for Solving the Problems The inventors of the present invention conducted extensive research to solve the above problems and discovered that a specific composition, when used as an adhesive for bonding components that transmit or diffuse light, does not generate air bubbles or cracks and has excellent adhesion, refractive index, heat resistance and high refraction, thereby completing the present invention. That is, the present invention is as follows. 1.A. Highly refractive metal oxide particles B. Cyclic siloxane compounds having two or more epoxy groups in the molecule C. At least one selected from polyfunctional thiol compounds and acid anhydrides D. At least one selected from alicyclic epoxy compounds and epoxy group-containing silane coupling agents An adhesive composition comprising: 2.A. The adhesive composition described in 1, wherein the highly refractive metal oxide is zirconium oxide. 3.B. The adhesive composition according to 1 or 2, wherein the cyclic siloxane compound having two or more epoxy groups in the molecule is a cyclic siloxane compound having three and / or four epoxy groups. 4.C. The adhesive composition according to any one of items 1 to 3, wherein at least one selected from a polyfunctional thiol compound and an acid anhydride is a polyfunctional thiol compound. 5.C. The adhesive composition according to any one of items 1 to 4, wherein the multifunctional thiol compound is a tri- or higher functional multifunctional thiol compound. 6.D. The adhesive composition according to any one of items 1 to 5, wherein at least one selected from the group consisting of alicyclic epoxy compounds and epoxy group-containing silane coupling agents is an epoxy group-containing silane coupling agent. Effect of the Invention

[0006] The adhesive of the present invention exhibits the remarkable effect of providing an adhesive composition that is free from the generation of bubbles or cracks after bonding and that is excellent in adhesion, refractive index, heat resistance and high refractive index. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] The present invention is an adhesive composition containing A. high refractive index metal oxide particles, B. a cyclic siloxane compound having two or more epoxy groups in the molecule, C. at least one selected from a polyfunctional thiol compound and an acid anhydride, and D. at least one selected from an alicyclic epoxy compound and an epoxy group-containing silane coupling agent.

[0008] The adhesive of the present invention contains the following components A to D. Each component will be described in order below. <A. High refractive index metal oxide particles> The A. high refractive index metal oxide particles used in the present invention are particles made of a material having a refractive index of 2.0 or more. Examples thereof include one or more particles composed of Ta2O5, TixOy, ZrO2, and composites thereof. An example of TixOy is TiO2. Since it is used to transmit and disperse various lights, it is necessary to be colorless particles. The average particle size is preferably 5 to 50 nm, more preferably 5 to 15 nm. In addition, the content of the A. high refractive index metal oxide particles in the solid content of the adhesive is preferably 50.0 to 90.0% by mass, more preferably 70.0 to 80.0% by mass.

[0009] <B. Cyclic siloxane compound having two or more epoxy groups in the molecule> As the cyclic siloxane compound having two or more epoxy groups in the molecule, the number of Si-O units (equal to the number of silicon atoms forming the siloxane ring) forming the siloxane ring is not particularly limited. From the viewpoint of improving crack resistance, the number of Si-O units is preferably 2 to 12, more preferably 4 to 8. The formula weight of the cyclic siloxane compound having two or more epoxy groups in the molecule is not particularly limited, but from the viewpoint of improving the crack resistance of the cured product, it is preferably 100 to 3,000, more preferably 180 to 2,000. The weight average molecular weight of the siloxane compound is calculated from the molecular weight in terms of standard polystyrene measured by the GPC (gel permeation chromatography) method. In addition, the B. cyclic siloxane compound having two or more epoxy groups in the molecule in the solid content of the adhesive is preferably 0.5 to 15.0% by mass, more preferably 0.5 to 5.0% by mass.

[0010] The number of epoxy groups in the cyclic siloxane compound having two or more epoxy groups in the molecule is not particularly limited as long as it is 2 or more. Among them, from the viewpoint of improving the crack resistance of the cured product, 2 to 4 (2, 3, or 4) are preferred. The epoxy equivalent of the cyclic siloxane compound having two or more epoxy groups in the molecule is not particularly limited, but from the viewpoint of improving the crack resistance of the cured product, it is preferably 180 to 2,000, more preferably 180 to 1,500, and even more preferably 180 to 1,000. The epoxy equivalent is a value measured in accordance with JIS K7236. The epoxy group contained in the cyclic siloxane compound having two or more epoxy groups in the molecule is not particularly limited, but from the viewpoint of improving the crack resistance of the cured product, it is preferably an alicyclic epoxy group, and among these, it is particularly preferably a cyclohexene oxide group. As a cyclic siloxane compound having two or more epoxy groups in a molecule, for example, a group having an epoxy group or an alkyl group, which may be the same or different, is bonded to the Si atom of the Si-O unit constituting the siloxane ring. Furthermore, two or more groups having an epoxy group are bonded in one molecule. Of these, it is preferable that two to four groups having an epoxy group are bonded.

[0011] The group containing an epoxy group is a group containing at least one epoxy group (oxirane ring), and examples thereof include a group in which at least one double bond of a linear or branched aliphatic hydrocarbon group having a carbon-carbon unsaturated double bond, such as an alkenyl group, has been epoxidized; and a group in which at least one double bond of a cyclic aliphatic hydrocarbon group having a carbon-carbon unsaturated double bond (for example, a cycloalkenyl group; a cycloalkenylalkyl group such as a cyclohexenylethyl group, etc.) has been epoxidized.

[0012] More specifically, examples include a 1,2-epoxyethyl group (epoxy group), a 1,2-epoxypropyl group, a 2,3-epoxypropyl group (glycidyl group), a 2,3-epoxy-2-methylpropyl group (methylglycidyl group), a 3,4-epoxybutyl group, a 3-glycidyloxypropyl group, a 3,4-epoxycyclohexylmethyl group, a 2-(3,4-epoxycyclohexyl)ethyl group, etc. Among these, a group in which at least one double bond of a cyclic aliphatic hydrocarbon group having a carbon-carbon unsaturated double bond has been epoxidized is preferred. Examples of the alkyl group include linear or branched alkyl groups having 1 to 20 carbon atoms such as methyl group, ethyl group, propyl group, isopropyl group, butyl group, hexyl group, octyl group, isooctyl group, decyl group, dodecyl group and the like. Among them, linear or branched alkyl groups having 1 to 10 carbon atoms are preferred.

[0013] Examples of the cyclic siloxane compound having two or more epoxy groups in the molecule include silsesquioxane having two or more epoxy groups in the molecule. More specifically, for example, 2,4-di[2-(3-{oxabicyclo[4.1.0]heptyl})ethyl]-2,4,6,6,8,8-hexamethyl-cyclotetrasiloxane, 4,8-di[2-(3-{oxabicyclo[4.1.0]heptyl})ethyl]-2,2,4,6,6,8-hexamethyl-cyclotetrasiloxane, 2,4-di[2-(3-{oxabicyclo[4.1.0]heptyl})ethyl]-6,8-dipropyl-2,4,6,8-tetramethyl-cyclotetrasiloxane, 4,8-di[2-(3-{oxabicyclo[4.1.0]heptyl})ethyl]-2,6-dipropyl-2,4,6,8-tetramethyl-cyclotetrasiloxane, 2,4,8-tri[2-(3-{oxabicyclo[4.1.0]heptyl})ethyl]-2,4,6,6,8-pentamethyl-cyclotetrasiloxane, 2,4,8-tri[2-(3-{oxabicyclo[4.1.0]heptyl})ethyl]-6-propyl-2,4,6,8-tetramethyl-cyclotetrasiloxane, 2,4,6,8-tetra[2-(3-{oxabicyclo[4.1.0]heptyl})ethyl]-2,4,6,8-tetramethyl-cyclotetrasiloxane. As the cyclic siloxane compound having two or more epoxy groups in the molecule, for example, commercially available products such as trade name X-40-2678, KR-470 (above, Shin-Etsu Chemical Co., Ltd.) can be obtained.

[0014] <C. At least one selected from polyfunctional thiol compounds and acid anhydrides> (Polyfunctional thiol compound) The polyfunctional thiol compound C used in the present invention is a compound having two or more thiol groups in one molecule. Specific examples of such C. thiol compounds include ethylene glycol bis(3-mercaptopropionate), diethylene glycol bis(3-mercaptopropionate), tetraethylene glycol bis(3-mercaptopropionate), 1,2-propylene glycol bis(3-mercaptopropionate), diethylene glycol bis(3-mercaptobutyrate), 1,4-butanediol bis(3-mercaptopropionate), 1,4-butanediol bis(3-mercaptobutyrate) (Carends MTBD1). , 1,8-octanediol bis(3-mercaptopropionate), 1,8-octanediol bis(3-mercaptobutyrate), hexanediol bisthioglycolate, trimethylolpropane tris(3-mercaptopropionate), trimethylolpropane tris(3-mercaptobutyrate) (Karenz MTTPMB), trimethylolpropane tris(3-mercaptoisobutyrate), trimethylolpropane tris(2-mercaptoisobutyrate), trimethylolpropane tristhioglycolate, tris -[(3-mercaptopropionyloxy)-ethyl]-isocyanurate, trimethylolethane tris(3-mercaptobutyrate), pentaerythritol tetrakis(3-mercaptopropionate), pentaerythritol tetrakis(3-mercaptobutyrate)(Carenz MTPE1), pentaerythritol tetrakis(3-mercaptoisobutyrate), pentaerythritol tetrakis(2-mercaptoisobutyrate), dipentaerythritol hexakis(3-mercaptopropionate), dipentaerythritol Examples of the dipentaerythritol hexakis include 2-mercaptopropionate, dipentaerythritol hexakis(3-mercaptobutyrate), dipentaerythritol hexakis(3-mercaptoisobutyrate), dipentaerythritol hexakis(2-mercaptoisobutyrate), pentaerythritol tetrakisthioglycolate, dipentaerythritol hexakisthioglycolate, 1,3,5-tris(3-mercaptobutyryloxyethyl)-1,3,5-triazine-2,4,6(1H,3H,5H)trione, etc. Preferably, a polyfunctional compound having three or more functional groups is preferable.

[0015] (Anhydride) The anhydride used in this embodiment is not particularly limited. For example, 1,2,3,6-tetrahydrophthalic anhydride, hexahydrophthalic anhydride, 4-methylhexahydrophthalic anhydride, methylbicyclo[2.2.1]heptane-2,3-dicarboxylic anhydride, bicyclo[2.2.1]heptane-2,3-dicarboxylic anhydride, glycerin bisanhydrotrimellitate monoacetate, etc. can be used. These may be used alone or in combination of two or more as necessary. In addition, at least one selected from C. polyfunctional thiol compounds and anhydrides contained in the solid content of the adhesive is preferably 0.5 to 10.0% by mass, more preferably 0.5 to 5.0% by mass in total. From the viewpoint of heat resistance, polyfunctional thiol compounds are preferred.

[0016] <D. At least one selected from alicyclic epoxy compounds and epoxy group-containing silane coupling agents> (Alicyclic epoxy compound) The alicyclic epoxy compound is a compound having one or more alicyclic epoxy groups. The alicyclic epoxy compound in the present invention has a structure in which a ring is formed and an epoxy bond is bridged between two adjacent carbon atoms. In addition, a compound having one or more alicyclic epoxy groups may further have an epoxy group other than the alicyclic epoxy group. The ring is preferably an aliphatic ring in which methylene groups are cyclically bonded, and more preferably has a cyclobutane, cyclopentane, cyclohexane, or cycloheptane structure. Furthermore, a compound having a linear alkyl group, a branched alkyl group, an alkylene group, or a vinyl group bonded to a carbon atom of such an aliphatic ring having an epoxy group, or a compound having an alicyclic epoxy structure in which an aliphatic ring having an epoxy group is bonded to another compound may also be used.

[0017] Specific examples of such alicyclic epoxy compounds include 3,4-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate, 1,2-epoxy-4-vinylcyclohexane, 1,2-epoxy-1-methyl-4-(1-methylepoxyethyl)cyclohexane, 3,4-epoxycyclohexylmethyl methacrylate, 4-(1,2-epoxyethyl)-1,2-epoxycyclohexane adduct of 2,2-bis(hydroxymethyl)-1-butanol, ethylene bis(3,4-epoxycyclohexanecarboxylate), oxydiethylene bis(3,4-epoxycyclohexanecarboxylate), 1,4-cyclohexanedimethyl bis(3,4-epoxycyclohexanecarboxylate), 3-(3,4-epoxycyclohexylmethoxycarbonyl)propyl 3,4-epoxycyclohexanecarboxylate, and ε-caprolactone-modified 3′,4′-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate. Among the alicyclic epoxy compounds, 3,4-epoxycyclohexylmethyl, 3,4-epoxycyclohexanecarboxylate, and ε-caprolactone-modified 3',4'-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate are preferably used because they have suitable curability and are relatively inexpensive to obtain. As the alicyclic epoxy compound, one type of alicyclic epoxy compound may be used alone, or different types may be used in combination. As the alicyclic epoxy compound, commercially available products can be used, and examples thereof include the "Celloxide (registered trademark)" series and "Cyclomer (registered trademark)" sold by Daicel Corporation, and the "Cyracure UVR" series sold by The Dow Chemical Company, each under their respective trade names.

[0018] (epoxy group-containing silane coupling agent) The epoxy group-containing silane coupling agent can be a compound having an epoxy group and an alkoxysilyl group. The epoxy group-containing silane coupling agent may contain only one epoxy group or may contain multiple epoxy groups, and may contain only one alkoxysilyl group or may contain multiple alkoxysilyl groups.

[0019] When the epoxy group-containing silane coupling agent contains only one alkoxysilyl group, the silane coupling agent is SiR 1 a R 2 b (OR 3 ) c (OH) 4-a-b-c Here, R 1 , R 2 , R 3 are all directly bonded to silicon atoms. 1 is an epoxy group-containing group, R 2 and R 3 are each independently an alkyl group, a is an integer of 1 to 3, b is an integer of 0 to 2, and c is an integer of 1 to 3. When any of a, b, and c is 2 or more, multiple R 1 may be different from each other, and multiple R 2 may be different from each other, and multiple (OR 3 ) may be different from each other.

[0020] R 1 The epoxy group-containing group in is not particularly limited as long as it contains an epoxy group, and examples thereof include a glycidoxy group-containing group and a cycloalkene oxide (alicyclic epoxy group)-containing group. The glycidoxy group and the cycloalkene oxide may be bonded to a silicon atom via a linking group such as an alkylene group (preferably an alkylene group having 1 to 10 carbon atoms). 1 It is preferred that R contains only one epoxy group. 1Examples of the epoxy group-containing group in R include a glycidoxy group, a 3-glycidoxypropyl group, an 8-(glycidoxy)-n-octyl group, a 3,4-epoxycyclohexyl group, and a 2-(3,4-epoxycyclohexyl)ethyl group. 1 It is preferable that the epoxy group contained in is not too far from the silicon atom, and for example, a glycidoxy group or a cycloalkene oxide is preferably bonded directly to the silicon atom or bonded to the silicon atom via an alkylene group having 1 to 6 carbon atoms.

[0021] R 2 and R 3 The alkyl group of R preferably has 1 to 6 carbon atoms, more preferably 1 to 4 carbon atoms, and further preferably 1 to 3 carbon atoms. 2 Preferred examples of the OR group include a methyl group, an ethyl group, an n-propyl group, and an isopropyl group. 3 ) preferably includes a methoxy group, an ethoxy group, an n-propoxy group, and an isopropoxy group. Furthermore, a is preferably 1 or 2, and more preferably 1. b is preferably 0 or 1, and more preferably 0.

[0022] When the epoxy group-containing silane coupling agent contains a plurality of alkoxysilyl groups, the silane coupling agent can be a polymer-type multifunctional epoxy group-containing silane coupling agent (hereinafter, sometimes simply referred to as "polymer-type silane coupling agent"). The polymer-type silane coupling agent has a structure in which an epoxy group-containing group and an alkoxysilyl group-containing group are bonded to an organic polymer chain, and can contain a plurality of alkoxysilyl groups and a plurality of epoxy groups in one molecule. Note that the organic chain of the polymer-type silane coupling agent does not include polysiloxane. Since the polymer-type silane coupling agent can thus have a plurality of alkoxysilyl groups and epoxy groups in one molecule, many reaction points with the resin or the support are formed, and the adhesion of the resin layer to the support can be increased.

[0023] Furthermore, the content of D. at least one selected from alicyclic epoxy compounds and epoxy group-containing silane coupling agents in the solid content of the adhesive is preferably 10.0 to 30.0 mass %, more preferably 15.0 to 25.0 mass %. From the standpoint of heat resistance, it is preferable to use an epoxy group-containing silane coupling agent.

[0024] (Other ingredients) Other components that may be further contained in the adhesive of the present invention include a curing agent, a curing catalyst, a stabilizer, and the like.

[0025] (Method of using the adhesive of the present invention) The adhesive of the present invention is used to bond two members selected from optically transparent materials such as high refractive index transparent glass, transparent resin sheets, etc. In this case, the highly refractive metal oxide particles contained in the layer made of the adhesive of the present invention increase the refractive index of the adhesive layer itself. This allows light emitted from a light source such as an LED to be efficiently dispersed by the sheet member made up of the above two members and the adhesive layer. EXAMPLES

[0026] (Adhesive manufacturing method) The raw materials listed below were weighed out in the prescribed amounts into a pressure-reducing Kolben so that the solid content of each raw material after solvent distillation would be as shown in Table 1, and mixed by stirring. The mixture was then cooled to 50°C for 1 hour under reduced pressure with a diaphragm pump to distill off the MEK (methyl ethyl ketone) and the ethanol and water solvents contained in the siloxane polymer, to prepare each adhesive. <Highly refractive metal oxide particles> Zircostar ZP-158 (Nippon Shokubai, zirconia nanoparticle MEK dispersion, particles content 70% by mass) <Cyclic siloxane compound having two or more epoxy groups in the molecule> KR-470 (Shin-Etsu Chemical) <Multifunctional thiol compounds> Karenz MTPE1 (tetrafunctional thiol compound) (Showa Denko) <Acid anhydride> Rikacid HH (Carboxylic acid anhydride) (Shin-Nippon Rika Co., Ltd.) <Alicyclic epoxy compounds> Celloxide 2000 (Daicel Chemical Industries, Ltd.) <Epoxy group-containing silane coupling agent> 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane <Silicone> Siloxane polymer X-22-3701E (Shin-Etsu Chemical) <Siloxane polymer> 29.8 parts by mass of tetraethoxysilane (product name: high-purity ethyl orthosilicate, Tama Chemical Industry Co., Ltd.), 14.3 parts by mass of hexamethyldisiloxane (reagent, Kishida Chemical), and 44.8 parts by mass of ethanol were mixed with stirring, to which 9.8 parts by mass of ion-exchanged water and 1.0 part by mass of 1 N hydrochloric acid were added and heated at 50°C for 1 hour to prepare a polysiloxane solution.

[0027] Evaluation method (zirconia compatibility) Initial Evaluation Other components were mixed into the zirconia MEK dispersion, and the appearance before distilling off the solvent was visually evaluated for cloudiness. Next Stage Evaluation Before the solvent was distilled off, the sample was turned into a film on a hot plate and visually evaluated for the occurrence of cloudiness. ○ Neither stage was cloudy × Cloudy at any stage

[0028] (Presence or absence of air bubbles) The pieces were attached to each other as described below for evaluating adhesion, and heated to 150° C. on a hot plate, and visually inspected for the generation of bubbles.

[0029] (viscosity) Evaluated using a B-type viscometer (model name: LVDV-I+, BROOKFIELD) (25°C) ○ Within the range of 10,000 to 100,000 cps × Outside the range of 10,000~100,000cps

[0030] (Adhesiveness) The adhesive was applied to a transparent glass plate with a bar coater to a thickness of about 10 μm, and the transparent glass plate was laminated. After heating and curing at 150° C. for 4 hours, the tensile shear load parallel to the adhesive surface was measured according to JIS K 6850 (1999). 〇 It does not peel off even when pulled parallel to the adhesive surface by hand. × When pulled parallel to the adhesive surface by hand, the adhesive peels off.

[0031] (Heat resistance) The coating was applied to a transparent glass plate using a bar coater to a thickness of approximately 10 μm, and the transparent glass plate was laminated. After heating and curing at 150°C for 4 hours, the plate was heated on a hot plate at 150°C for 40 hours, after which the presence or absence of cracks and color change were visually checked. No cracks or color changes occurred. × No cracks occurred, but the color changed

[0032] (Refractive Index) A film with a thickness of approximately 1 μm was formed on a transparent glass substrate using a spin coater, and after heating at 150°C for 4 hours, the reflectance was measured in the range of 400 to 800 nm using an Otsuka Electronics FE-3000. The nkCauchy dispersion equation was quoted as an approximation equation for the wavelength dispersion of the refractive index, and the unknown parameters were found from the actual measured values ​​of the absolute reflectance spectrum using the nonlinear least squares method to calculate the refractive index at a wavelength of 550 nm.

[0033] [Table 1] JPEG0007631026000002.jpg93170

[0034] According to Examples 1 to 6 and Example 7, which are examples according to the present invention, suitable effects were obtained with respect to zirconia miscibility, the presence or absence of bubbles, viscosity, adhesion, heat resistance (color change) (cracks), and refractive index. However, when the acid anhydride of Example 6 is used, and when the alicyclic epoxy compound of Example 8 is used, the heat resistance (color change) decreases, but they can be used in applications that are not exposed to high temperatures and do not require heat resistance. In contrast, Comparative Examples 1 and 2, which did not contain a cyclic siloxane compound having two or more epoxy groups in the molecule but contained silicone or siloxane, showed poor miscibility with zirconia or generated bubbles. Also, Comparative Example 3, which simply did not contain a cyclic siloxane compound having two or more epoxy groups in the molecule, showed insufficient adhesion.

Claims

1. A. Highly refractive metal oxide particles B. Cyclic siloxane compound having two or more epoxy groups in the molecule C. At least one selected from a polyfunctional thiol compound and an acid anhydride D. At least one selected from alicyclic epoxy compounds and epoxy group-containing silane coupling agents An adhesive composition comprising: The content of A is 50.0 to 90.0 mass% of the solid content of the adhesive composition, The content of B is 0.5 to 15.0 mass % of the solid content of the adhesive composition, The content of C is 0.5 to 10.0 mass % of the solid content of the adhesive composition, The content of D is 10.0 to 30.0 mass % of the solid content of the adhesive composition.

2. A. The adhesive composition of claim 1, wherein the highly refractive metal oxide is zirconium oxide.

3. B. The adhesive composition according to claim 1 or 2, wherein the cyclic siloxane compound having two or more epoxy groups in the molecule is a cyclic siloxane compound having three and / or four epoxy groups.

4. C. The adhesive composition according to any one of claims 1 to 3, wherein at least one selected from the group consisting of a polyfunctional thiol compound and an acid anhydride is a polyfunctional thiol compound.

5. C. The adhesive composition according to any one of claims 1 to 4, wherein the multifunctional thiol compound is a trifunctional or higher multifunctional thiol compound.

6. D. The adhesive composition according to any one of claims 1 to 5, wherein the at least one selected from the group consisting of alicyclic epoxy compounds and epoxy group-containing silane coupling agents is an epoxy group-containing silane coupling agent.

Citation Information

Patent Citations

  • High temperature-resistant adhesive for microelectronic devices

    CN109181605A

  • JP1974021410A

  • Intermediate film for laminated glass and laminated glass

    JP1996026784A

  • Curable composition

    JP2008291137A

  • Transparent adhesive for refractive index regulating optical member, transparent adhesive layer for optics, manufacturing method of transparent adhesive for refractive index regulating optical member and manufacturing method of transparent adhesive layer for optics

    JP2009120726A